Atypical parathyroid adenoma - Anikode Subramanian Ramaswamy; Thinakaran Vijitha; B N Kumarguru; Prashant Basavaraj Mahalingashetti (Wolters Kluwer Medknow Publications, 2017)
Parathyroid lesions clinically manifest themselves in the form of primary hyperparathyroidism most of the times. Parathyroid adenoma constitutes one of the important causes of the same. Although rare, they pose considerable diagnostic dilemma to the pathologist. A 50-year-old female presented to the surgical outpatient of our hospital with a history of recurrent pancreatitis. Clinical examination revealed a mass in the neck which was radiologically demonstrated as right inferior parathyroid mass. The same mass was surgically excised and histopathological features are discussed in this report.